The UK prevalence of hereditary haemorrhagic telangiectasia and its association with sex, socioeconomic status and region of residence: a population-based study - Donaldson, J.W.; McKeever, Tricia M.; Hall, Ian P.; Hubbard, R.B.; Fogarty, Andrew W. (BMJ Publishing Group, 2014)
Background Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant genetic disorder of aberrant blood vessel development characterised by arteriovenous malformations. HHT is associated with significant morbidity due to complications including epistaxis, gastrointestinal bleeding and stroke. We explored the hypothesis that a diagnosis of HHT is associated with sex, socioeconomic status and geographical location.Methods We used The Health Improvement Network, a longitudinal, computerised general practice database covering 5% of the UK population to calculate prevalence estimates for HHT stratified by age, sex, socioeconomic status and geographical location.Results The 2010 UK point prevalence for HHT was 1.06/10 000 person years (95% CI 0.95 to 1.17) or 1 in 9400 individuals. The diagnosed prevalence of HHT was significantly higher in women compared with men (adjusted prevalence rate ratio (PRR) 1.53, 95% CI 1.24 to 1.88) and in those from the most affluent socioeconomic group compared with the least (adjusted PRR 1.74, 95% CI 1.14 to 2.64). The PRR varied between different regions of the UK, being highest in the South West and lowest in the West Midlands (adjusted PRR for former compared with latter 1.86, 95% CI 1.61 to 2.15).Conclusions HHT prevalence is more common in the UK population than previously demonstrated, though this updated figure is still likely to be an underestimate. HHT appears to be significantly under-diagnosed in men, which is likely to reflect their lower rates of consultation with primary care services. There is under-diagnosis in patients from lower socioeconomic groups and a marked variation in the prevalence of diagnosis between different geographical regions across the UK that requires further investigation.